The Impact of Mutual Influence of Organisations and Information Technology Systems (International Journal of Scientific Research and Management (IJSRM), 2023)
This study was instrumental in justifying the mutual influence of organizations and information technology systems. Specifically, the paper examine the extent to which information technology tools are utilized to maximizing efficiency in business organizations., and explore the challenges affecting the utilization of information technology. The paper used the qualitative approach applying survey design. The study purposively selects fifty (50) entrepreneurs and business owners to form the sampled subjects. The instrument for data collection used for this study was the close ended questionnaire. Conclusively, it was found that computers, mobile phone, computer software and internet are utilized for maximizing efficiency of business organizations to a high extent. Also, it was revealed that challenges such infrastructural deficiencies, lack of maintenance culture, poor/no access to the internet and lack of skilled and competent ICT personnel has affected the utilization of information technology to a high extent. It was recommended that business owners should embrace training policy to upgrade the knowledge and skills of their employees on ICT.